(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the concept of adding rational numbers, a fundamental operation in mathematics. Rational numbers, which include integers, fractions, and terminating or repeating decimals, are essential for both theoretical and practical applications in mathematics. The paper examines the rules, properties, and methods of addition, supported by illustrative examples, to ensure a comprehensive understanding. The pedagogical importance of teaching addition of rational numbers in primary and secondary education is highlighted, alongside its applications in real life, business, and science. The article concludes by emphasizing the role of rational number addition in developing strong mathematical foundations.